27-run nonisomorphic three level orthogonal arrays: Identification, evaluation and projection properties - Evangelaras H.; Koukouvinos C.; Lappas E. (Utilitas Mathematica, 2011)
In this paper we construct all possible three level orthogonal arrays with 27 runs and 3 ≤ q ≤ 13 columns and present those that are nonisomorphic. A discussion on the novelty and the superiority of many of the designs found in terms of isomorphism and generalized minimum aberration is made. The GWP k profile criterion is introduced to evaluate nonisomoprhic arrays as screening designs.